2019
DOI: 10.1002/nau.24033
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of regenerative medicine and tissue engineering for the treatment of stress urinary incontinence in female patients

Abstract: Stress urinary incontinence (SUI) is an age health‐related issue that generates interest due to its considerable public health burden and the controversies surrounding treatment. It is highly prevalent affecting 30–40% of all women during their lifetime. Midurethral slings are the standard of gold standard treatment for female patients with SUI. They have excellent short‐term cure rates; however, their efficacy tends to decrease over time and patients often report urinary incontinence recurrence. This paper ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Both undifferentiated and differentiated stem cells have been used to treat UI [ 28 ]. The different stem cell sources that have been already used include bone marrow, human cord blood, amniotic fluid, and muscle [ 29 ]. Injection of muscle-derived stem cells into the urethra sphincter muscle improved UI-related outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both undifferentiated and differentiated stem cells have been used to treat UI [ 28 ]. The different stem cell sources that have been already used include bone marrow, human cord blood, amniotic fluid, and muscle [ 29 ]. Injection of muscle-derived stem cells into the urethra sphincter muscle improved UI-related outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of ADSCs for SUI treatment has already demonstrated positive outcomes regarding muscular tissue regeneration and improving the EUS function by increasing the expression of alpha smooth muscle actin (α‐SMA) and elastin genes and providing the ability of myoblastic differentiation 25,26 . IHC evaluations have revealed that the transplanted cells possess the ability to differentiate into muscle lineages by expressing myoblast progenitor cell markers, angiogenesis, and nerve regeneration; they also found that the cells at the injection site caused a bulge in the lumen of the urethra 15,27,28 . Furthermore, studies indicated that MDSCs, isolated in large quantities, could be employed to significantly raise leak point pressure in SUI animal models as well as to increase muscle contraction, regenerate muscle fiber and blood vessels, and the neuromuscular junction formation 29‐31 .…”
Section: Discussionmentioning
confidence: 99%
“…Standard therapies often provide symptomatic relief, but do not target against the underlying etiology, and exhibit tremendous patient-to-patient variability of results, limited success, and procedure-related complications. More clinical trials of new treatment methods involving the required number of patients and with evaluation the long-term results of therapeutic methods for the incontinence correction should be encouraged [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%